Merancang Kesuksesan: Pelatihan Business Model Canvas Untuk Meningkatkan Motivasi Kewirausahaan - Mirhamida Rahmah; Chamdan Purnama; Dinda Fatmah (CV. Multi Kreasi Media, 2024)
Education is crucial for nation-building and enhancing community welfare. Hence, every country strives to design strategic educational policies. This underscores the importance of collaboration to boost productivity and reduce unemployment among vocational school graduates. The outreach team conducted an initial survey at the Sunan Ampel Vocational Islamic High School Plus Skills (MAPK) in Kertosono and identified the need for entrepreneurship training programs for students. The aim is to assist them in acquiring the understanding, knowledge, skills, and attitudes necessary to become successful entrepreneurs. This program aims to encourage MAPK Sunan Ampel, Kertosono students to prepare themselves as successful entrepreneurs post-graduation, with hopes of benefiting themselves and the surrounding community. The training method to be used is integrated guidance through information dissemination, discussion, demonstration, and guided practice. Through this training, students will be guided to develop their business ideas into practical business plans using the Business Model Canvas (BMC). The results of this outreach indicate that participants expressed that this method provided a deeper understanding of business aspects and helped them plan their businesses more structuredly. The use of BMC assists them in designing businesses more structuredly and practically.